The impact of different IPV-OPV sequential immunization programs on hepatitis A and hepatitis B vaccine efficacy - Shiyi Chen; Yuping Zhao; Zhiyao Yang; Ying Li; Hongyuan Shi; Ting Zhao; Xiaolei Yang; Jing Li; Guoliang Li; Jianfeng Wang; Zhifang Ying; Jingsi Yang (Taylor & Francis Group, 2022)
In recent years, the Global Polio Eradication Initiative has gradually implemented a global shift in polio immunization programs. Few studies cover polio immunization program impacts on the efficacy of other vaccines. This study investigated whether polio immunization programs affected hepatitis A (HepA) and hepatitis B (HepB) vaccination efficacy. Serum samples were collected from 968 infants before the first dose of polio vaccine, 28 days after completing primary polio immunization, and at 24 months old. Infants were classified into six polio immunization program groups: 1sIPV+2bOPV, 2sIPV+1bOPV, 2sIPV+1tOPV, 1cIPV+2bOPV, 2cIPV+1bOPV, and 2cIPV+1tOPV (sIPV: Sabin inactivated poliovirus vaccine; cIPV: Salk inactivated poliovirus vaccine; b, bivalent; t, trivalent; OPV, oral polio vaccine). No significant differences existed in antibody titers against HepA virus (anti-HAV) among the polio immunization program groups at any of the three time points (pre-first dose [p = 0.412], 28 days after primary immunization [p = 0.676], 24 months old [p = 0.556]). Before the first dose (p = 0.178) and at age 24 months (p = 0.987), no significant differences existed in HepB surface antibody (HBsAb) titers between the six polio immunization program groups). Twenty-eight days after primary immunization, no significant difference existed in HBsAb titers between groups after Bonferroni correction. Following HepA and HepB immunization, anti-HAV and HBsAb positivity reached > 98% in all groups, reflecting effective immunization. Our data suggest that different polio immunization programs did not affect HepA and HepB vaccine efficacy; HepA and HepB vaccines maintained high effectiveness irrespective of polio immunization program. This trial was registered on Clinical Trials.gov: NCT03614702.